Perceived Decrease in Workplace Security Since the Beginning of the COVID-19 Pandemic: The Importance of Management Styles and Work-Related Attitudes - Wojtkowska, Anna; Tyburski, Ernest; Skalacka, Katarzyna; Gasiorowska, Agata (Frontiers in Psychology, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has reduced the sense of security of people in everyday life. The efforts of managers in the workplace to minimize the health risks and economic damage, however, can provide the employees with a greater sense of security. The aim of this study was to identify the types of workplace responses to the pandemic outbreak with respect to the characteristics of employees and their employers accomplishing the differences in subjective sense of workplace security before the pandemic and during the outbreak. Three hundred and thirty-seven Polish employees completed an online survey during the first 2 weeks of the COVID-19 pandemic in March 2020. Using the cluster analysis, we identified four subgroups of employees differing in their sense of workplace security, work-related psychological factors, and perceived management styles of their supervisors. Employees led by developers and executive managers sustained a high sense of work security and positive attitude to work, while those led by compromisers and deserter managers suffered from the highest drop of subjective security. In this study, we proposed how employees can be protected from overreactions and unnecessary panic in a time of global crisis by virtue of the psychological competences of their supervisors and employers.